VOICE OF PLAY : Miskitu childrens speech and song on the atlantic coast of nicaragua / Amanda Minks - Minks , Amanda (2013)
"Voices of Play "is a study of multilingual play and performance among Miskitu children growing up on Corn Island, part of a multi-ethnic autonomous region on the Atlantic Coast of Nicaragua.